Anti-Rheumatic Properties of Gentiopicroside Are Associated With Suppression of ROS-NF-κB-NLRP3 Axis in Fibroblast-Like Synoviocytes and NF-κB Pathway in Adjuvant-Induced Arthritis - Wang, Meiling; Li, Hongyan; Wang, Yanfang; Hao, Yanfei; Huang, Yanan; Wang, Xinlin; Lu, Yongying; Du, Yuan; Fu, Fenghua; Xin, Wenyu; Zhang, Leiming (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is among the most prevalent forms of autoimmunity. Gentiopicroside (Gent) is an iridoid glucoside derived from the Gentiana Macrophylla Pall which is used in traditional Chinese medicine to treat RA. The present study was designed to explore the ability of Gent to combat RA and to explore the molecular basis for such anti-RA activity both in vitro using tumor necrosis factor alpha (TNF-α)-stimulated human RA fibroblast-like synoviocytes (RA-FLS) and in vivo using a rat adjuvant-induced arthritis (AIA) model. We found that Gent was able to significantly reduce the swelling of joints and arthritic index scores, with corresponding reductions in synovial inflammatory cell infiltration, synovial hyperplasia and bone erosion in treated AIA rats. Importantly, Gent 200 mg/kg reduced thymus index in AIA rats, but had no effect on spleen index and body weight, it revealed that Gent was relatively safe at the dose we chose. We further found that Gent was able to suppress the TNF-α-induced proliferation and migration of RA-FLS cells. This suppression was attributed to the ability of Gent to block NOD-like receptor protein 3 (NLRP3), apoptosis-associated speck-like protein containing a CARD (ASC), and caspase-1, thereby disrupting the activation of the NLRP3 inflammasome. Consistent with such suppression, Gent led to a significant decrease in IL-1β secretion by treated cells. Furthermore, this reduction in NLRP3 inflammasome activation was also associated with decreases in the activation of nuclear factor (NF-κB), the production of reactive oxygen species (ROS), and the expression of inflammatory IL-6. Together these findings indicate that Gent can suppress the ROS-NF-κB-NLRP3 axis to alleviate RA symptoms.